Communication in Passing On The Tradition Of Dressing In Almunawar Arab Village - Aulia Nazila; Yenrizal; Gita Astrid (Universitas Muhammadiyah Palu, 2026)
This study aims to find out the forms of communication and analyze the values of local wisdom contained in the tradition of dressing in Almunawar Arab Village. The type of research used is field research with a qualitative approach that is descriptive. The data collection methodology used in this study is observation, documentation and interviews. The primary data sources in this study are community leaders or village elders and religious leaders who play a role in the preservation of Islamic values in Arab villages, while secondary data sources are obtained from documentation obtained from the results of the research. The technique for analyzing data is through three stages, 1) data reduction, 2) data presentation and 3) drawing conclusions or verification. Based on the results of research on Communication in Inheriting the tradition of dressing in Almunawar Arab Village, it can be concluded that cultural communication has a very important role as the main medium in transmitting and maintaining the values of local wisdom. The process of inheriting the tradition of dressing does not occur instantly, but through continuous social interaction in people's daily lives, both in the family and community environments. Cultural communication that takes place in Almunawar Arab Village is carried out through various forms, such as advice, example, habituation, and participation in social and religious activities. Parents and community leaders act as cultural mediators who not only convey dress codes, but also explain the meanings contained in them, such as the value of politeness, cultural identity, and religiosity. Through this process, the young generation not only knows, but also understands and internalizes these values as part of their identity.